From Transition to Europeanization: Reforming Administration in the Baltic States - Koski, Susanna (My University, 2009)
The purpose of this study has been to evaluate and compare public administration reforms in the Baltic countries. After the Soviet Union’s communism collapsed in the 1990’s, the Baltic states gained back their independency. The new environment with strong European influences necessitated the Baltic states to reform their public administration to correspond to the new situation and the external strains. The Baltic states had common goals in reforming their administration. They were all striving towards membership of the European Union. This study focuses on the transition period’s reforms. I have chosen the Baltic states as case countries because of their common historical background and orientation to European Union. These circumstances create an interesting framework for reforming public administration. The communist administration or culture did not value democracy, and it was generally rather different than modern administration. The theoretical framework for reforming administration concentrates on the transition theory, internationally defined principles of good governance and Europeanization. The principles of good governance function as guiding values in the actual reforming process. They help directing reform measures right. Good governance is the cornerstone of a democratic society. Good governance has a legislative basis and it guides the everyday operation of civil servants. Most of all, it directs the development in political strategies. Beside transition and good governance, the states’ striving towards membership of the European Union is important. During the transition phase, the Baltic countries oriented themselves to the European Union’s membership and based their administration to the structure that the EU necessitated. Most important of these prerequisites was a democratic and modern society. The administration’s reforms were strongly guided by EU and other international organizations. This study is a comparative evaluation. I contemplate the Baltic states as cases, and the administrations’ reforms are compared to each other. The states are comparable. Because of their similarities, the case study is possible by individual approach as well as by taking the environment in consideration. I have collected the research material mostly of international organizations’ official documents and reports concerning the Baltic states. This study demonstrates that by reforms good governance is similar in the Baltic countries administration. The administrations’ reforms represent the values of good governance. The realized reforms are betweenwhiles similar and dissimilar. The Baltic countries started from the same circumstances and proceeded on their individual paths towards the EU. Each of these countries has demonstrated the effectiveness of their reforms by becoming EU member states. The communist administration’s legacy has influenced the public administration reforms.
Keywords: Baltia; reform; administration; good governance; transition; European Union; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|